MASUKNYA AGAMA ISLAM DI PALEMBANG PADA MASA KERAJAAN SRIWIJAYA ABAD VII MASEHI - Kabib Sholeh (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Theory of the entry of Islam in Palembang there is a 7th century AD opinion and there is also a opinion of the 13th and 16th century AD. The purpose of this study was to analyze the entry path of Islam in the center of Sriwijaya kingdom, analyze the factors driving the entry of Islam by Arab traders and its relationship with Sriwijaya in the 7th century AD. This study uses historical method, while the steps are first, heuristic or data collection process or source, both data verification or the process of selecting valid and authentic source, the third interpretation which means the process of interpreting data that has been collected by synthesizing, and finally historiografi is writing history. In conclusion in this study is Islam entered in Palembang in the 7th century AD, at the same time at the time Palembang as the center of the maritime kingdom Sriwijaya Buddhist-patterned. Islam entered at the center of Sriwijaya brought by traders from Arab directly through the sea lane of the Arabian sea - the Strait of Bengal - Strait of Malacca - Strait of Bangka and enter into Palembang through the river Musi. The driving factor of the entry of Muslim traders in Sriwijaya due to trade or economic factors with Sriwijaya. Furthermore, there was also a cooperative relationship between the rulers of Sriwijaya and the Arab rulers during the Muawaiyah dynasty. The entry of Islam in Palembang was well received by the rulers of Sriwijaya, while the evidence of the existence of Islam in Palembang in the 7th century AD is evidenced by records from China and the remains found around Palembang. Keywords: Islamic Religion, Palembang, Sriwijaya Kingdom